Enhancing Information Retention of Forensic Science Students: Incorporating a Simulated Crime Scene Practicum in the College Classroom - Byrne, David S (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The purpose of this research was to investigate whether crime scene simulations benefit the learning process in terms of retention of knowledge. By providing a real-word experience via the Applied Learning pedagogy, the comprehension of the basic foundations of forensic science were indeed retained and reinforced through the incorporation of a mock crime scene in the classroom. A total of 50 undergraduate students majoring in criminal justice participated and were evaluated using three different assessment measures employed throughout the practicum: feedback, reflection, and debriefings. This qualitative research uncovered that students’ retention of the theories and concepts continued past the midterm examination while the instructor benefited from a multi-assessment approach to gauging student performance. Additionally, this research also found that learners benefited in ways beyond the scope of this study; they also came away with practical realizations relating to the benefits of collaboration and an understanding of how this course prepares them for careers in law enforcement.